2021
DOI: 10.1093/pubmed/fdab102
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: health impact of staying at home, social distancing and ‘lockdown’ measures—a systematic review of systematic reviews

Abstract: Background To systematically review the evidence published in systematic reviews (SR) on the health impact of staying at home, social distancing and lockdown measures. We followed a systematic review approach, in line with PRISMA guidelines. Methods In October 2020, we searched the databases Cochrane Database of Systematic Reviews, Ovid Medline, Ovid Embase and Web of Science, using a pre-defined search strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
100
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 52 publications
2
100
0
6
Order By: Relevance
“…In a span of a few months, coronavirus disease 2019 (COVID-19) has developed into a full-scale global pandemic of epic proportions that affects all age groups with considerable mortality, various sequelae in survivors, and grave socio-economic impact on society ( 1 , 2 ). Involvement of multiple body systems and organs, including the lung, gastrointestinal tract, liver.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a span of a few months, coronavirus disease 2019 (COVID-19) has developed into a full-scale global pandemic of epic proportions that affects all age groups with considerable mortality, various sequelae in survivors, and grave socio-economic impact on society ( 1 , 2 ). Involvement of multiple body systems and organs, including the lung, gastrointestinal tract, liver.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of multiple body systems and organs, including the lung, gastrointestinal tract, liver. blood vessels, heart, nervous system, and kidneys, has been reported in patients with COVID-19 ( 1 ). The varied presentations of this disease are under intense study in the hope of better understanding its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have shown that in the general population, the COVID-19 pandemic is strongly associated with poor mental health outcomes [22][23][24]. Other reviews have documented the deleterious impact of the epidemic among those living with mental illness [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Starting in China in the end of 2019 (2), it spread to all countries in the world, with waves occurring at different moments of time in each locality. A number of interventions were implement all over the world, such as travel ban, social distancing and mandatory mask use (3,4), and its effects have been discussed in different works, which generally concluded that they were effective in reducing the growth of cases and deaths (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%